Training materials on climate-smart crop production by National Agricultural Extension Center - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The training materials consist of eight modules. For the first time a specific module on climate change and GHG emissions in rice production has been included. The materials have been distributed to extension staff of 25 provinces to instruct over 50,000 rice farmers/year, starting spring-summer season in 2020.